Áp dụng mô hình Modified Jones với dữ liệu chéo: Nghiên cứu hành vi quản trị lợi nhuận của các công ty niêm yết khi phát hành thêm cổ phiếu - Nguyễn Công, Phương (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
The objective of this study is to apply the cross-sectional Modified Jones Model to identify earning management of seasoned equity issuers in Vietnam. To attract investors, the issuers that raise capital through seasoned equity offerings often report higher net income prior to the offering. Based on the positive approach and by using Modified Jones' (1995) accruals model, the results show that 75% of companies in the sample adjust discretionary accruals to report higher net income prior to the seasoned equity offering. This finding, on the one hand, provides initial evidence of managers' behavior of seasoned equity issuers in Vietnam and confirms previous findings on the opportunistic behavior of managers in order to reduce the cost of capital. On the other hand, application of the modified Jones model is suggested with the cross-sectional data.
Keywords: Modified Jones Model; Earnings management; Seasoned equity issuers; Accruals